An Interpretative Phenomenological Analysis of Ghanaian Trainee Teachers’ Motivation to Major in the English Language: Implications for Classroom Pedagogy - Daniel Arkoh Fenyi; Richard Morrison (CV. Literasi Indonesia, 2022)
This study aims to investigate the motivation with which all the 18 final year English-major students of a College of Education in the Western North Region of Ghana made the ‘choice’ to major in the English language. This qualitative study employed a semi-structured one-on-one interview and focus group discussions as the data collection instruments. The data collected were subjected to a thematic analysis. The outcome of the study reveals that the learners admit that motivation plays a crucial role in their choice to major in the English language. Seven thematic areas were identified as the motivation for the choice. These are; self-esteem and fulfillment, communicative functionality, global competitiveness, technology, home and family factors, academic relevance, and the teacher factor. It is revealed that the stakeholders of education, such as teachers, curriculum planners and designers, developers of teaching and learning materials, principals, and school managers, should be aware of the motivation of the students for ‘choosing’ to major in a particular course [such as English] to design programs, curriculum, teaching and learning activities and materials that would best sustain and enhance the interest of the learner in the program.